MHC-mismatched synovial mesenchymal stem cell injections delay knee osteoarthritis progression through hepatocyte growth factor secretion in rats - Tsukasa Kitahashi; Kentaro Nakamura; Ryo Kogawa; Ichiro Sekiya (PLoS ONE, 2025)
Background Knee osteoarthritis (OA) currently lacks disease-modifying treatments. While autologous mesenchymal stem cell (MSC) transplantation has shown promise, its limitations have led to growing interest in allogeneic MSC therapy. The aim of this study was to clarify the functional role of hepatocyte growth factor (HGF) in the chondroprotective effects of synovial MSCs transplanted under fully major histocompatibility complex (MHC)-mismatched allogeneic conditions in a rat model. Methods Synovial MSCs were isolated from the knees of ACI rats and transfected with either Hgf siRNA or control siRNA. HGF knockdown was confirmed at both the mRNA and protein levels. Chondrogenic capacity was assessed by evaluating the cartilage pellet size after in vitro differentiation. OA was surgically induced in Lewis rats by anterior cruciate ligament transection (ACLT). At one week post-surgery, the rats (n = 20 knees/group) received weekly intra-articular injections of one of the following for 7 weeks: (1) vehicle control (medium alone), (2) control siRNA-treated MSCs, or (3) Hgf siRNA-treated MSCs (1 × 10⁶ cells). At 8 weeks post-injection, cartilage degeneration was evaluated using macroscopic and histological Osteoarthritis Research Society International (OARSI) scoring. Results Transfection with Hgf siRNA reduced Hgf gene expression to 30% of the control levels and significantly decreased HGF protein secretion. HGF knockdown impaired in vitro chondrogenic differentiation, resulting in a reduced cartilage pellet size. In vivo, treatment with control siRNA-treated MSCs significantly delayed OA progression compared to the vehicle group, while Hgf siRNA-treated MSCs demonstrated diminished therapeutic efficacy, indicating reduced chondroprotective effects when HGF secretion was suppressed. Conclusions Synovial MSCs derived from ACI rats effectively delayed OA progression in Lewis rats despite the full MHC mismatch. HGF secretion played a critical role in mediating these chondroprotective effects. These findings highlight HGF as a key therapeutic effector in MSC-based treatment of OA under immunologically mismatched allogeneic conditions.